2023
DOI: 10.1101/2023.02.16.528819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational Prediction of PROTAC-compatible Protein-Protein Interfaces by Molecular Docking

Abstract: Proteolysis targeting chimeras (PROTACS) are ligands that can mediate interaction between a protein target and a E3 ligase, forming a ternary complex bound to the ubiquitination machinery, leading to target degradation. This technology has become an exciting new avenue for therapeutic development, with currently two PROTACS in clinical trials targeting cancer. Nonetheless, several PROTAC drug discovery campaigns still rely on serendipity. Here, we describe a general and efficient protocol which combines restra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…While some groups have developed tools for this purpose [32][33][34][35][36] , they are typically not general because they require that the PROTAC molecule be known a priori. Within our group we developed PROTACability 25 , which by-passes this constraint and achieves satisfactory accuracy but fails to produce high quality solutions. Thus, there is significant room for improvement and a general tool that uses minimal information and achieves high prediction quality would significantly impact the field of PROTAC-based drug discovery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While some groups have developed tools for this purpose [32][33][34][35][36] , they are typically not general because they require that the PROTAC molecule be known a priori. Within our group we developed PROTACability 25 , which by-passes this constraint and achieves satisfactory accuracy but fails to produce high quality solutions. Thus, there is significant room for improvement and a general tool that uses minimal information and achieves high prediction quality would significantly impact the field of PROTAC-based drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…DockQ: To evaluate the similarity between the experimental structures and the predicted structures from AF-Multimer, the DockQ criteria were employed 28 . In short, DockQ provides a continuous score from 0 to 1 (with 1 being perfect similarity) which takes into account the fraction of conserved native contacts, RMSD of the target protein and the interface RMSD between a reference structure and a predicted structure 25 . This metric can be employed either quantitatively or qualitatively, with possible classifications being inaccurate (0-0.229), acceptable (0.23-0.49), medium (0.50-0.799) or high quality(0.80-1) predictions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative tools applied in TPD include PatchDock, [96][97] FRDOCK, [98][99] MOE packages, [100][101][102][103] ClusPro, [104] and LightDock. [105] The in silico determination of ternary complexes calls for a thorough understanding of protein-protein conformations. However, resolving ligand (PRO-TAC) geometry is also needed to create accurate models, as discussed in the following section.…”
Section: Protein-protein Dockingmentioning
confidence: 99%
“…We take care not to overstate this observation, as recent analyses have indicated that current versions of AlphaFold are not useful for predicting the final conformation of E3 ligase/ternary complexes formed by induced proximity reagents. 20 However, the potential for differential molecular recognition, together with slight biochemical selectivity of CPI-1612 for EP300, motivated us to explore this HAT ligand's degrader capabilities.…”
mentioning
confidence: 99%